Activation of ZnCl2 and KOH Carbon from Bark of Salak Wedi as a Material for Making Supercapacitor Electrodes - Ardianti, Aprillia Dwi (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2022)
An activated carbon is a potential material that can be used as electrodes in super capacitors. It has a higher energy density than batteries and fuel cells, and a higher power density than conventional capacitors. This study was carried out by using activated carbon from the bark of salak wedi with various graded activators such as ZnCl2 and KOH. The physical characteristics of the activated carbon from the bark of salak wedi were analyzed using a Scanning Electron Microscope (SEM) to see its powder morphology. While, X-ray diffraction (XRD) isÂ used to examine the structure of the bark of activated carbon thatÂ that has the potential to make electrodes of super capacitors . The results of SEM with graded activation had fewer pores, were not evenly distributed and tended to agglomerate compared to the activated carbon sample of salak bark which was activated once